IMPLEMENTASI PEMBELAJARAN MANDIRI UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH PADA MATA KULIAH KALKULUS INTEGRAL - Rani Farida Sinaga (MES: Journal of Mathematics Education and Science, 2023)
The purpose of this study was to determine the implementation of the implementation of independent learning to improve students' problem-solving abilities. This study refers to qualitative research procedures with a descriptive approach, namely research that aims to provide a quality picture of the subjects and research objects studied. This research was conducted in the Teaching and Education Faculty of HKBP Nommensen University, especially the Mathematics Program. This research was conducted in the odd semester of the 2022/2023 academic year. The subjects of this study were students of the Mathematics Education Study Program, namely Stambuk 2020, a total of 40 students. The object of this research is the implementation of independent learning in integral calculus courses on the subject of indeterminate integrals. From the results of the study, it was obtained that the problem-solving abilities of students after independent learning were shown by data on each aspect of the data that had increased, the average value increased from 52.34 to 76.74. This shows that there has been an increase in students' problem-solving abilities after implementing independent learning. When viewed from student learning completeness, we can also see that independent learning is also considered effective when student learning completeness exceeds 70% of the total students in the class, where in this study the learning completeness was 77%. Independent learning can help and train students in solving problem solving skills independently. In other words, the habit of exploring ideas independently will be able to develop mathematical problem solving abilities.